Microbiome, Transcriptome, and Metabolomic Analyses Revealed the Mechanism of Immune Response to Diarrhea in Rabbits Fed Antibiotic-Free Diets - Wang, Jie; Fan, Huimei; Xia, Siqi; Shao, Jiahao; Tang, Tao; Chen, Li; Bai, Xue; Sun, Wenqiang; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Microbiology, 2022)
In this study, diarrhea was induced in rabbits by feeding them antibiotic-free feed. The gut provides important defense against the barriers of the body, of which the duodenum is an important part to help digest food and absorb nutrients. However, the mechanisms underlying the roles of the gut microbiome and fecal metabolome in rabbit diarrhea caused by feeding an antibiotic-free diet have not been characterized. Recently, only a single study has been conducted to further characterize the antibiotic-free feed additives that caused diarrhea in weaned rabbits. The multi-omics techniques, including 16S rRNA sequencing, transcriptome sequencing, and LC-MS analysis, were combined to analyze the gut microbial compositions and functions. They also determined the fecal metabolomic profiles of diarrhea in rabbits caused by feeding antibiotic-free feed. The results showed that the liver, duodenal, and sacculus rotundus tissues of diarrhea rabbits were diseased, the composition of intestinal microbes was significantly changed, the diversity of intestinal microbes was decreased, and the distribution of intestinal microbe groups was changed. Functional analysis based on the cluster of GO and KEGG annotations suggested that two functional GO categories belonged to the metabolism cluster, and five KEGG pathways related to the metabolic pathways were significantly enriched in diarrhea rabbits. Moreover, real-time quantitative PCR (RT-qPCR) was used to verify the significant expression of genes related to diarrhea. Metabolomics profiling identified 432 significantly differently abundant metabolites in diarrhea rabbits, including amino acids and their derivatives. These amino acids were enriched in the tryptophan metabolic pathway. In addition, the functional correlation analysis showed that some altered gut microbiota families, such as Parasutterella, significantly correlated with alterations in fecal metabolites. Collectively, the results suggested that altered gut microbiota was associated with diarrhea caused by antibiotic-free feed additives in weaned rabbit pathogenesis.